2016
DOI: 10.1007/s11606-015-3569-y
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Testing an Electronic Measure of Screening Colonoscopy Overuse in a Large Integrated Healthcare System

Abstract: BACKGROUND: Most existing performance measures focus on underuse of care, but there is growing interest in identifying and reducing overuse. OBJECTIVE: We aimed to develop a valid and reliable electronic performance measure of overuse of screening colonoscopy in the Veterans Affairs Health Care System (VA), and to quantify overuse in VA. DESIGN: This was a cross-sectional study with multiple cross-sections. SUBJECTS: U.S. Veterans who underwent screening colonoscopy between 2011 and 2013. MAIN MEASURES: Overus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 22 publications
2
62
0
Order By: Relevance
“…However, prior data suggest that many older adults with comorbidities, limited life expectancy, and previous normal screening results may not benefit from ongoing screening colonoscopies. 1,5,6,7,8,9,14,15 Moreover, these patients may be at increased risk for screening-related harms and burdens. Thus, experts recommend that screening decisions be individualized in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior data suggest that many older adults with comorbidities, limited life expectancy, and previous normal screening results may not benefit from ongoing screening colonoscopies. 1,5,6,7,8,9,14,15 Moreover, these patients may be at increased risk for screening-related harms and burdens. Thus, experts recommend that screening decisions be individualized in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, one unintended consequence has been overuse of low-value CRC screening, particularly in older and less healthy patients who have limited life expectancy. 1,5,6,7,8,9 …”
Section: Introductionmentioning
confidence: 99%
“…3 They found that, compared to results obtained from manual record review, the electronic measure was highly specific (97 %) for overuse, but was not sensitive (20 %). To some extent, the fact that the electronic measure had low sensitivity reflects limitations in the ability to electronically ascertain screening indication.…”
Section: S3mentioning
confidence: 97%
“…The studies by Saini et al . 9 and Farmer et al . 10 in this issue of JGIM also show the potential of eCQMs for monitoring overuse and patient-reported outcomes, respectively.…”
Section: Advance Measurement Of Care Processesmentioning
confidence: 92%